The Mediation Effect of Emotional Intelligence on Knowledge-Based Human Resource and Organizational Commitment of The Employee Performance Retail Modern In Tangerang City - Tan Hadi (Syntax Literate, 2022)
The role of the workforce as one of the resources in the business world is getting clearer, various concepts have been born to encourage the motivation of the workforce, which is expected to have good performance. Performance or achievement are the results obtained from jobs or activities over a period of time. The purpose of this article is to analyze the effect of Knowledge Based Human Resources (KB) on employee performance (PE), the effect of organizational commitment (OC) on PE, the effect of KB on Emotional Intelligence (EI), OC on EI, EI mediates the relationship between OC and PE, and EI mediate the relationship between KB and PE in modern retail in the city of Tangerang. Cross-sectional quantitative research. The results obtained were analyzed using the SMART-PLS method, the results showed that both OC and EI had a significant positive effect on PE, while KB had a positive effect on PE, while OC and KB significantly affected EI. For the mediating impact of EI, it turns out that EI strengthens the relationship between OC and PE, while EI weakens the relationship between KB and PE. From this study it was found that EI is the most dominant factor influencing PE compared to the other two factors, this shows the need to increase EI for Modern Retail employees by building a system that includes EI indicators in the process of hiring, learning and development. The second factor that also has a significant influence on PE is OC, this shows that the Modern Retail organization must strengthen the work culture and organizational values ​​so that it can increase the strong desire for employees to continue to work on behalf of the organization and remain as members of the organization.